Role of Lifestyle Modification through Dietary Changes to Endometrial Receptivity on Infertility Women and Obesity with Polycystic Ovary Syndrome - Julianto Witjaksono; Fiastuti Witjaksono; Andhika A. Perdana (Indonesian Socety of Obstetrics and Gynecology, 2021)
Abstract Objective: To investigate the effect of lifestyle modification on endometrial receptivity of obese women with polycystic ovary syndrome using ultrasonography.Methods: This observational study was conducted at Dr. Cipto Mangunkusumo General Hospital Jakarta from August 2019 to May 2020. A total of 14 subjects were participated in this study. The subjects were advised to get nutrition counseling by nutritionist and then followed up the endometrial profiles for 6 months by ultrasonography.Results: A total 19 subjects were received nutrition counseling by Clinical nutritionist, but then, only 14 subjects were evaluated the endometrial study by Ultrasonography. There were several significant result between before and after treatment some subjects such as calories, body weight, body mass index, waist circumference (p<0.05) and type of the endometrial vascular zone, endometrium volume, and vascular flow index by ultrasonography (p<0.05). In this study, no significant results have been found on the correlation between dietary changes and changes in endometrial receptivity profiles.Conclusion: No significant correlation was observed between changes in anthropometrics and daily calorie intake with changes in endometrial vascular zones.Keywords: endometrial receptivity, obese, polycystic ovary syndrome, ultrasonography. Abstrak Tujuan : Untuk mengetahui pengaruh modifikasi gaya hidup pada reseptivitas endometrium perempuan obesitas dengan sindrom ovarium polikistik menggunakan ultrasonografi.Metode: Penelitian observasional ini dilakukan di Rumah Sakit Umum Cipto Mangunkusumo Jakarta dari Agustus 2019 hingga Mei 2020. Sebanyak 14 subjek berpartisipasi dalam penelitian ini. Semua subyek disarankan untuk mendapatkan konseling gizi oleh ahli gizi dan dilakukan observasi profil endometrium selama 6 bulan dengan ultrasonografi.Hasil: Sebanyak 19 subjek menerima konseling gizi oleh ahli gizi klinis, tetapi kemudian, hanya 14 subjek yang dievaluasi profil endometrium dengan Ultrasonografi. Ada beberapa hasil yang signifikan antara sebelum dan sesudah perawatan beberapa subjek seperti kalori, berat badan, indeks massa tubuh, lingkar pinggang (p<0,05) dan tipe zona vaskular endometrium, volume endometrium, dan indeks aliran vaskular dengan ultrasonografi (p <0,05). Dalam penelitian ini, tidak ditemukan hasil yang signifikan pada korelasi antara perubahan pola makan dan perubahan dalam profil reseptivitas endometrium.Kesimpulan: Tidak ada korelasi yang signifikan antara perubahan antropometrik dan asupan kalori harian dengan perubahan zona vaskular endometrium.Kata kunci: endometrium, obesitas, reseptivitas, sindrom ovarium polikistik, ultrasonografi